Fuel Cells – Polymer-Electrolyte Membrane Fuel Cell | Flow Fields - Celik, Erman; Karagoz, Irfan (Elsevier, 2024)
One of the most important parts determining fuel cells’ performance is the flow channels. A well-designed flow area provides homogeneous reactant distribution, good heat and water management, and high performance in a fuel cell. Although most of the flow field designs are created by modifying the fundamental flow areas, it has been seen that quite innovative solutions have been put forward. In this chapter, firstly, the main flow fields and their main characteristics will be introduced, then the flow field designs obtained from modifying the fundamental flow fields and innovative flow fields such as bio-inspired flow fields and advanced flow field designs will be explained. The performance characteristics of the proposed designs are generally determined on a single cell using experimental and sometimes numerical methods. Therefore, most of the proposed flow fields need to be tested in real-life conditions as cell stacks. It has been observed that the new generation flow fields have emerged as structures that will allow more proactive control of the in-cell flow, such as multiple inlet and outlet manifolds, multi-layered flow channels, and reservoirs. © 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Bioinspired design; Bioinspired flow filed; Flow areas; Flow channels; Flow field design; Flow patterns; Fuel cells; PEM fuel cells